Peranan Dan Gaya Kepemimpinan Hubungannya Dengan Efektivitas Kerja Karyawan : Kasus Restoran Bakmi Japos Cabang Bogor - Maydiana, Cahya; Saleh, Amiruddin (Sodality: Jurnal Sosiologi Pedesaan, 2008)
The role and leadership style are factors wich determine the employees performance in getting company’s goal. Leader’s behaviour is an important factor to motivate the employees. The leadership style is one of an input. The other inputs are culture, law, politic, economic, social and technology. They have to be processed to increase the skill’s employees so the effectiveness of job employees will be created. The aims of this research are: (1) to explain the role and style of leadership that played by Bakmi Japos Restaurant’s manager, (2) to explain the level of employees job effectiveness at Bakmi Japos Restaurant, (3) to analyze the correlation between the role and leadership’s style manager with employees job effectiveness at Bakmi Japos Restaurant, (4) to explain the relation among internal, external and situational factors with the role and style of leadership’s manager at Bakmi Japos Restaurant. The population was all employees of Bakmi Japos Restaurant. Sample were 38 persons and taken by sensus technique. The results of this research were: (1) The employees so enough satisfied with four leadership role and effective communicator as a mostly role while the employees so enough agree that five leadership style are needed to reach restaurant’s goal with democratic style inclined, (2) The employees work effectively, (3) An amount the role and leadership style have a hihgly significant (p